THE EFFECTIVENESS OF THE FREE NUTRITIOUS MEAL PROGRAM AT BINA BANGSA INTEGRATED ISLAMIC ELEMENTARY SCHOOL IN SERANG CITY IN 2025 - Saleh, Muhammad; Fatwanti, Devi; Muhtarom, Ali (LPPM Universitas Bina Bangsa, 2025)
The Free Nutritious Meal Program (MBG) is a program introduced by the Indonesian government in 2025 to address nutrition issues in children, reduce stunting rates, and improve the quality of basic education. This study aims to evaluate how effective the implementation of the MBG program is at the elementary school level through a literature review approach. The findings of this study show that MBG has a good influence on children's nutritional status, including reducing stunting rates as well as increasing students' concentration and attendance at school. The program also contributes to easing the economic burden on families and empowering local entrepreneurs. However, in its implementation, the program still faces several challenges, such as uneven distribution of food, lack of facilities in schools, and differences in understanding of nutrition in the community. This study concludes that MBG has significant potential in creating a healthy and quality young generation, as long as it is supported by good management